(untitled) (Cadernos de Sociomuseologia, 2016)
This article aims to analyze globally the work between 1993 and 2012 by the Journal of Sociomuseology (44 volumes published), who was born to serve the education and the critical reflection that was proposed by the Post-Graduation program in Sociomuseology. During these 19 years the jornal have always been at the center of their activity the publication of texts that somehow could contribute to the reflection and consolidation of museology as social science but having the Sociomuseology as a guide. This option results in the truth of the social and cultural context in which they were born the first training programs which were designed to accommodate each and every person who already working in museums, had by reference to ecomuseology and / or new museology and of course concerns related to participation, identity, dialogic processes of acting, which in one way or another if they could relate to the content of the Declaration of Santiago Round Table 1972 and 1984 Quebec Declaration. Keyword: Sociomuseology: Journal of Sociomuseology